Pancreas as Delayed Site of Metastasis from Papillary Thyroid Carcinoma - Tunio, Mutahir A. (Hindawi Publishing Corporation, 2013)
Introduction. Follicular variant (FV) papillary thyroid carcinoma (PTC) has aggressive biologic behavior as compared to classic variant (CV) of PTC and frequently metastasizes to the lungs and bones. However, metastasis to the pancreas is extremely rare manifestation of FV-PTC. To date, only 9 cases of PTC have been reported in the literature. Pancreatic metastases from PTC usually remain asymptomatic or manifest as repeated abdominal aches. Associated obstructive jaundice is rare. Prognosis is variable with reported median survival from 16 to 46 months. Case Presentation. Herein we present a 67-year-old Saudi woman, who developed pancreatic metastases seven years after total thyroidectomy and neck dissection followed by radioactive iodine ablation (RAI) for FV-PTC. Metastasectomy was performed by pancreaticoduodenectomy followed by sorafenib as genetic testing revealed a BRAF V600E mutation. She survived 32 months after the pancreatic metastasis diagnosis. Conclusion. Pancreatic metastases are rare manifestation of FV-PTC and are usually sign of extensive disease and conventional diagnostic tools may remain to reach the diagnosis.